Increasing Activity By Students Creativity in Drawing Classes - Khalimov Mohir Karimovich; Mashrabbayev Hayotullo Numonjonovich (Genius Publishing Group, 2022)
The article describes methods for increasing the activity of students by involving them in creativity in drawing lessons, as well as methodological recommendations for this.
Keywords: Knowledge; skills; competencies; spatial imagination